PRODUKSI HIDROGEN DENGAN PROTON EXCHANGE MEMBRANE (PEM) ELECTROLYSER AIR SEBAGAI SUMBER ENERGI - , ADITYA YULIHADI PURNAMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Application of renewable energy technologies is critical to reducing our dependence on fuel oil (BBM) and reduce CO2 emissions to slow global warmin. In 2012, Indonesia in the 12 largest emitting 500 million metric tons of CO2 in the world. In the future, expect a lot of hydrogen is produced as a transportation fuel that does not contribute to global warming. As one of the most attractive alternative energy, hydrogen used in fuel cells to generate electricity or internal combustion motors directly. Fuel cells produce electricity and water from the reaction between hydrogen and oxygen. This reaction occurs without burning. In this research, the process of electrolysis of water by reversing the function of the fuel cell (reverse - fuel cell). Electrolysis of water using a Proton Exchange Membrane (PEM) is a process of reverse - fuel cell. Since the PEM fuel cell is the generator it self. PEM elektroliser used to produce hydrogen gas and oxygen 99.99% pure, with a variation of the current (1,5A